Dampak Perubahan Penggunaan Lahan Pertanian Terhadap Komoditi Unggulan Akibat Pembentukan Kabupaten Buton Selatan - La Ode Restele; Anita Indriasary; Hazriani Hazriani; irfan Ido; Jamal Harimuddin (Universitas Halu Oleo, 2023)
Rapid development has an impact on increasing land use change. The establishment of South Buton Regency in 2014 triggered an increase in development in Batauga District which resulted in the expansion of built-up land and changes agricultural land use. Changes in agricultural land use will affect agricultural productivity, especially leading commodities. This study aims to: (1) determine changes in agricultural land use in Batauga District due to the establishment of South Buton Regency; (2) know the impact of changes in agricultural land use on leading commodities. This study uses quantitative descriptive analysis methods and OBIA. The results of this study include: (1) Changes in agricultural land use due to the formation of South Buton Regency have changed from 3,119.26 acre previously to 2,971.64 acre in 2021; (2) Impact of changes in the use of agricultural land on superior commodities, namely commodities before formation become a base then become non-base after the formation of South Buton Regency and vice versa.. Keywords: Land Use Change, Agriculture, Leading Commodity